2021
DOI: 10.1177/2378023121992600
|View full text |Cite
|
Sign up to set email alerts
|

Who Wears the MAGA Hat? Racial Beliefs and Faith in Trump

Abstract: On the basis of a 2019 YouGov survey of white respondents ( n = 734), the impact of racial beliefs on support for Donald Trump was explored. The analysis revealed that in addition to racial resentment, white nationalism—a desire to keep the United States white demographically and culturally—was strongly related to faith in Trump. Analyses based on a 2019 Amazon Mechanical Turk survey yielded similar results and also showed that white nationalism increased willingness to wear a MAGA hat. Future research on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
(41 reference statements)
3
19
0
Order By: Relevance
“…The items have high internal reliability (α = .968) and load on a single factor (loadings range from .923 to .958). The previous research, based on a 2019 national-level YouGov survey, reported similar scale statistics (loadings range from .920 to .974, α = .974) (Graham et al 2020). See Table 4 for the question wording of each item.…”
Section: Independent Variablesmentioning
confidence: 57%
See 1 more Smart Citation
“…The items have high internal reliability (α = .968) and load on a single factor (loadings range from .923 to .958). The previous research, based on a 2019 national-level YouGov survey, reported similar scale statistics (loadings range from .920 to .974, α = .974) (Graham et al 2020). See Table 4 for the question wording of each item.…”
Section: Independent Variablesmentioning
confidence: 57%
“…Two measures of this construct are used in the analysis. First, general faith in Trump is drawn from previous research by Graham et al (2020) and measures support for the president’s leadership views, style, and efficacy. It is a mean index based on five Likert-type items (1= strongly disagree , 5 = strongly agree ) that asked respondents about their general attitudes toward President Trump (e.g., “I believe that President Trump will make America great again”).…”
Section: Methodsmentioning
confidence: 99%
“…Also, racial resentment and political conservatism are difficult to separate. In fact, nearly 20 years ago, Beckett and Sasson (2004, p. 54) argued that race was “the organizing principle of American politics.” The interrelationship between the two has only grown in recent years (Enders & Scott, 2019; Hochschild, 2018), with research demonstrating that racial resentment is related to identification as a conservative or Republican, the expression of anti‐democratic sentiments among Republicans, and votes for former President Trump (Bartels, 2020; Graham, Cullen, et al, 2021; Jones et al., 2020; Riley & Peterson, 2019; Shook et al., 2020; Smith, 2019). In this respect, there is disagreement about whether racial resentment measures racism or political values, and about whether controlling for political values is sufficient to isolate the anti‐Black dimension of racial resentment (Rabinowitz et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although voluminous research exists explaining Trump's 2016 surprise election, a common theme is that he drew much support by emphasizing white identity and outgroup hostility toward Blacks, immigrants, and Muslims (Fording & Schram, 2020;Graham et al, 2021;Jardina, 2019). Direct anti-Asian rhetoric from Trump was relatively sparse.…”
Section: Trump's Animus Toward Chinamentioning
confidence: 99%